The influence of sustainability reporting, gender diversity on future firm value and future firm performance - Azizah, Mia Nur; Puspawati, Dewita (Junal Ilmu Manajemen, 2025)
This study examines the effects of energy use management, water management, and gender diversity on the future performance and value of companies in the energy sector, focusing on those listed on the Indonesia Stock Exchange (IDX) between 2021 and 2022. A quantitative research design with descriptive analysis is applied. The sample is selected using purposive sampling, based on criteria such as the availability of sustainability reports. Secondary data is sourced from the sustainability reports of energy firms. The research explores future firm value, represented by Tobin's Q, and future firm performance, measured by Return on Assets (ROA), as dependent variables. The independent variables include energy consumption, water usage, and the proportion of female board members. Data is analyzed using SPSS, with descriptive statistics, assumption tests, and regression analysis. Findings suggest that energy use management has a positive effect on future firm value, whereas water management and gender diversity do not significantly influence firm value. On the other hand, both water management and gender diversity are positively linked to future firm performance. The study's scope is limited by its focus on the energy sector and the short time frame of analysis. Future research could broaden the scope and sample to enhance generalizability. The study recommends that companies adopt transparent and consistent sustainability practices to enhance performance and value, while suggesting that the government consider implementing mandatory sustainability reporting for firms listed on the IDX.